Parenting Patterns and Diabetes Mellitus Prevention in Children A Descriptive Analysis of Literature Studies - Rus Andraini (Health & Medical Sciences, 2026)
This study aims to analyze the role of parenting patterns in preventing diabetes mellitus in children through a descriptive literature review approach. The increasing prevalence of childhood obesity and unhealthy lifestyles has raised concerns about the early risk of metabolic disorders, including diabetes mellitus, making family based prevention strategies increasingly important. This research employed a qualitative research design using a descriptive approach through a literature study. Data were collected through systematic searches of relevant academic sources, including peer reviewed journal articles, scientific publications, and other scholarly documents discussing parenting patterns, childhood obesity, and diabetes prevention. The collected data were analyzed using a thematic analysis process that involved identifying key themes, reducing and categorizing relevant information, and interpreting the findings inductively to obtain a comprehensive understanding of the relationship between parenting and childhood metabolic health. The results indicate that parenting patterns significantly influence children’s health behaviors, particularly in shaping dietary habits, physical activity, and lifestyle routines that affect the risk of obesity and metabolic disorders. Positive parental involvement, health literacy, and supportive family environments contribute to healthier behavioral patterns that reduce the likelihood of developing diabetes mellitus in childhood. These findings emphasize that effective prevention strategies should prioritize family centered health promotion, parental education, and collaborative efforts involving families, healthcare providers, schools, and communities. In conclusion, this study contributes to the understanding that parenting patterns are fundamental determinants in shaping children’s health behaviors and play an essential role in early prevention strategies aimed at reducing the risk of diabetes mellitus in children.